Legal Effects of Environmental Taxation in Tackling Greenhouse Gas Emission in Nigeria: The Need for a Comprehensive Legal Framework - Kehinde, Adeola Olufunke; Ariyoosu, Dauda Adeyemi (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2024)
Reducing greenhouse gas emissions has emerged as a significant undertaking undertaken by nations worldwide, driven by the urgency to address the escalating global climate change and its widespread impacts. However, Nigeria has exhibited limited progress in tackling the challenges of climate change and other environmental issues inside its borders. This article focuses on examining environmental taxation as a potential strategy for addressing environmental concerns in Nigeria. It draws upon examples from several European countries that have effectively utilised environmental taxation as a means of achieving notable achievement in environmental protection. The study is relevant in the current context, as it is imperative to promptly explore strategies for overcoming the environmental difficulties faced by Nigeria. It is also crucial to promptly intensify the implementation of environmental taxation in Nigeria to effectively discourage individuals or entities from engaging in activities that contribute to environmental degradation. This measure will ultimately lead to a significant reduction in environmental pollution throughout the country, thereby addressing the issue of greenhouse gas emissions, which are primarily responsible for global climate change. The subject of environ mental taxes and their implications in addressing environmental concerns, particularly in the context of Nigeria, has garnered significant attention in academic discourse. Like many other nations, Nigeria has pressing environmental issues that necessitate the implementation of effective policies and regulations. In this regard, the role of environmental laws and their potential impact on mitigating climate change is the subject of scholarly investigation. This paper concludes by stating that there is no comprehensive legal framework on environmental taxation in Nigeria and thereby recommends a standardised law on environmental taxation.